EFFICIENCY OF THE TAX SYSTEM ON THE BASIS OF TRANSPARENCY AND REFORM - OLEINIKOVA, LUDMILA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The expediency is reasoned of creating a competitive environment in the context of globalization and limited factors of production, forcing countries to compete with each other and take measures to attract owners of factors of production by forming the optimal combination of institutional, public goods and tax preferences, where only tax preferences are not the key to success in competition, as opposed to general conditions of taxation in combination with infrastructural, institutional and public goods. Emphasis is placed on the rapid digitalization of economic processes and the globalization of even small businesses through online platforms that will significantly affect the struggle in the field of economic and institutional competition. It has been proven that it is already necessary to respond to new challenges which are associated with tax evasion, erosion of the tax base, a significant geographical gap between the location of factors of production and the jurisdiction of profit. It is established that the answers to these risks lie both in the plane of institutional readiness and in the plane of the effectiveness of the application of tax administration tools, including control, as well as the synergy of measures at the macro and micro levels. The variety of tools used in world practice to improve compliance with tax legislation is studied and their division into categories is indicated. The expediency of using mechanisms to ensure the transparency of the tax system is substantiated, along with measures to assure the transparency of taxpayers before the tax authorities at the national level, as well as mechanisms to provide accountability and transparency of the tax authorities themselves to the government, parliament and taxpayers. It is proposed, taking into account foreign experience, in addition to quantitative indicators of tax effectiveness, to use supplementary indicators that characterize the work of tax authorities, considering economy, effectiveness, efficiency, which will deepen the level of tax system performance.